Fabrication of silver nanoparticles–curcumin–agar nanocomposite film and its super antimicrobial activity. (1st January 2015) - Linh, Le Hoang; Taniike, Toshiaki; Trung, Nguyen Ba
This work explores a novel method for in–situ fabrication of silver nanoparticles (NPs) using hydrolysed agar as a reducing agent and matrix for the dispersion of silver NPs. UV–vis spectroscopy, FT–IR, X–ray diffraction (XRD) and TEM were used to confirm the formation, crystallisation, and size of the synthesised silver NPs, respectively. The result showed that the size of synthesised silver NPs was in the range of 15 to 20 nm. Curcumin ((1E, 6E)–1, 7–Bis(4–hydroxy–3–methoxyphenyl)–1, 6–heptadiene–3, 5–dione) with anti–bacterial, anti–oxidant, and wound healing properties was mixed with the solution of the agar–based silver NPs in order to improve anti–bacterial properties of the resulting material. Anti–bacterial tests for the synthesised silver NPs–curcumin–agar material for Gram (-) and Gram (+) bacteria demonstrated significant effects against both Escherichia coli and Staphylococcus aureus. Nanocomposite film of the silver NPs–curcumin–;agar material may fnd use for a wide variety of biomedical applications, such as cosmetic masks, anti–bacterial polymers for wound dressing and burn–treatment medicines.